COMMENTS ON AMERICAN COLLEGE OF CARDIOLOGY, AMERICAN HEART ASSOCIATION AND EUROPEAN SOCIETY OF CARDIOLOGY GUIDELINES (2006) FOR THE MANAGEMENT OF PATIENTS WITH ATRIAL FIBRILLATION - A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Comments on American College of Cardiology, American Heart Association and European Society of Cardiology Guidelines (2006) for the management of patients with atrial fibrillation.